Revealing Student’s Reading Interest through creative WhatsApp Status - Budiastuti, Riana Eka; Mulyadi, Dodi (Journal of English Teaching and Learning Issues, 2019)
Along with the rapid development of technology and digital era, this research investigated and reveal millennial students about their reading habit and interest. Specifically, this paper investigates about students’ reading interest through creative WhatsApp status.  This study was carried out by 18 students taking “Basic Reading” class and “Cultural Based Reading” class. It was conducted with descriptive qualitative method by using interview and observation of the students’ WhatsApp status screenshot. It is found that 89% students of English Department Universitas Muhammadiyah Semarang are more interested in reading fiction than the factual text. Besides, students also find that learning using experiment with social media is fun and challenging.